Synthesis and evaluation of antibacterial activity for a series of N-phthaloylglycine derivatives - Begum, Samreen; Nizami, Shaikh Sirajuddin; Saied, Sumayya; Shahid, Syed Muhammad; Basha, Fatima Zehra (European Journal of Chemistry, 2014)
Two series of N-phthaloylglycine derivatives were synthesized under Schotten-Baumann conditions. The first series consists of N-phthaloylglycine amides (4a-h), and the second one consists of benzimidazole derivatives of N-phthaloylglycine (6a-d). All the synthesized analogues were evaluated for their in vitro antimicrobial activity by using disc diffusion method. In the first series, compounds 4h (MIC, 0.5 mg/L), 4a (MIC, 0.6 mg/L), and 4e (MIC, 0.7 mg/L) were found to be the most potent against vancomycin-resistant Staphylococcus aureus (VRSA). Furthermore, three compounds i.e. 4g (MIC, 0.8 mg/L), 6b (MIC, 1.5 mg/L), and 4h (MIC, 1.6 mg/L) displayed good activity against methicillin-resistant Staphylococcus aureus (MRSA). All the synthesized compounds exhibited a wide range of antibacterial activity against all of the Staphylococcus aureus resistant strains tested. The structures of the synthesized compounds were characterized by IR, 1H NMR, 13C NMR and MS (EI).